2005
DOI: 10.1128/iai.73.6.3385-3393.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Monocyte Function in Microfilaremic Patients with Lymphatic Filariasis and Its Relationship to Altered Lymphoproliferative Responses

Abstract: Antigen-specific hyporesponsiveness to filarial antigens is a phenomenon observed in patent infection with lymph-dwelling filarial parasites of humans. This phenomenon has been attributed to a multitude of factors, one of which is altered monocyte function. To examine the role played by monocytes in filarial infection, we assessed the responses of monocytes obtained from normal and filarial parasite-infected individuals to both crude filarial antigen and purified recombinant filarial antigen WbSXP-1 and attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 52 publications
8
32
0
Order By: Relevance
“…Studies in humans and animal models have demonstrated that immune inhibition extends to many arms of the immune response, including DC (33,46), macrophages/monocytes (12,47), and T cells (7,48), and that parasites secrete numerous molecules to aid in this task (45). These and other studies indicate that the mechanisms of filarial suppression differ according to the stage of the life cycle, and that patency is a turning point at which maximal suppression occurs (17,(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans and animal models have demonstrated that immune inhibition extends to many arms of the immune response, including DC (33,46), macrophages/monocytes (12,47), and T cells (7,48), and that parasites secrete numerous molecules to aid in this task (45). These and other studies indicate that the mechanisms of filarial suppression differ according to the stage of the life cycle, and that patency is a turning point at which maximal suppression occurs (17,(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence during human infection that APC function is compromised (11,12), and rodent models of filarial infection have demonstrated a variety of mechanisms by which filarial parasites immunosuppress their host (13)(14)(15)(16)(17)(18)(19). Mosquito-borne Brugia malayi L3 larvae are able to down-regulate expression of MHC class I and class II on human Langerhans cells and to inhibit their ability to activate T cells in vitro (20), whereas the same parasites, if injected into the murine peritoneal cavity, induce suppressive nematode-elicited macrophages (NeM) 3 that are able to block T cell proliferative responses (21).…”
mentioning
confidence: 99%
“…According to the first method (29), subjects showing SI of Ͼ2 in response to CCA and Ͼ20 in response to PHA were considered subjects showing positive responses. In another method (13,25,26,27,29), median SI values between the different groups were compared as reported earlier for various infections including parasites.…”
Section: Demographicsmentioning
confidence: 99%
“…Preparation of cRNA, hybridization, and scanning of the U133A arrays were performed according to the manufacturer's protocol (Affymetrix, Santa Clara, CA). Briefly, 2 to 4 g of RNA was converted into double-stranded cDNA by reverse transcription using a cDNA synthesis kit (SuperScript Choice; Life Technologies, Gaithersburg, MD) with an oligo(dT) 24 primer containing a T7 RNA polymerase promoter site added 3Ј of poly(T) (Genset Oligos, La Jolla, CA). After secondstrand synthesis, biotin-labeled cRNA was generated from the cDNA sample by an in vitro transcription reaction supplemented with the Bioarray high-yield RNA transcription labeling kit (Enzo, Farmingdale, NY).…”
Section: Study Population (I) Pretreatmentmentioning
confidence: 99%
“…Purified monocytes from filaria-infected patients have recently been shown to function less well, based on measurement of phagocytosis or spreading in response to a bacterial stimulus (24).…”
mentioning
confidence: 99%